2014
DOI: 10.1371/journal.pone.0086397
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic and Recurrent Otitis Media–A Meta-Analysis

Abstract: Risk factors associated with chronic otitis media (COM) and recurrent otitis media (ROM) have been investigated in previous studies. The objective of this study was to integrate the findings and determine the possible risk factors for COM/ROM based on our meta-analysis. A comprehensive search of electronic bibliographic databases (PubMed, Embase, CNKI and Wanfang database) from 1964 to Dec 2012, as well as a manual search of references of articles, was performed. A total of 2971 articles were searched, and 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
137
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 64 publications
(67 reference statements)
19
137
2
6
Order By: Relevance
“…The influence of gender is controversial with some studies showing a higher prevalence in males [10,11], other studies in females [7], and the remainder failing to show an effect of gender on otitis media [4,5,8]. Our results showed that males were found to undergo tympanostomy tube insertion slightly more than females (55.1, 95% CI 49.1-61.0 vs. 44.9, 95% CI 39.0-50.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of gender is controversial with some studies showing a higher prevalence in males [10,11], other studies in females [7], and the remainder failing to show an effect of gender on otitis media [4,5,8]. Our results showed that males were found to undergo tympanostomy tube insertion slightly more than females (55.1, 95% CI 49.1-61.0 vs. 44.9, 95% CI 39.0-50.9, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown a statistically significant influence on the presence of otitis media [2,4], while others have failed to identify a relationship [5,11]. The likelihood that a child in the 8-12 year-old cohort had siblings in the home was increased compared to those in the younger group (OR 1.72, p = 0.03).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 telah melaporkan bahwa dari berbagai faktor risiko yang ada, alergi atau keadaan atopi merupakan salah satu faktor risiko yang dapat meningkatkan otitis media kronik (p<0,001; OR=1,36). Bozkus dkk.…”
unclassified